2014
DOI: 10.1080/15017419.2014.972449
|View full text |Cite
|
Sign up to set email alerts
|

Socio-material practices in classrooms that lead to the social participation or social isolation of disabled pupils

Abstract: Classrooms are comprised of people, relationships, tools, and technologies, which together constitute the socio-material practices of the classroom. This paper investigates how such socio-material practices influence disabled pupils' opportunities for participation in classroom activities. The paper draws on a qualitative observation study with 14 disabled pupils aged 11-15 years. An actor-network theory perspective was employed in this paper, and the analytical process was inspired by an interpretive content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Most of the existing research about children with disabilities and the use of assistive equipment is embedded in a dichotomy of disabled-not disabled and an individual deviation approach (Lancioni et al, 2004;Logan et al, 2001;Mulholland & McNeill, 1989). Findings in disability studies based on social and relational models of disability, technology, or education (Östlund, 2015;Söderström, 2016;Söderström & Ytterhus, 2010) identify students using assistive technical devices as competent, attentive, and responsive, and are thus partly in line with our study. However, these studies do not include students with severe disabilities and do not give special attention to bodily expressions and existential dimensions to the same extent that we do and Moser (2006) and Shakespeare (2006) recommend.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Most of the existing research about children with disabilities and the use of assistive equipment is embedded in a dichotomy of disabled-not disabled and an individual deviation approach (Lancioni et al, 2004;Logan et al, 2001;Mulholland & McNeill, 1989). Findings in disability studies based on social and relational models of disability, technology, or education (Östlund, 2015;Söderström, 2016;Söderström & Ytterhus, 2010) identify students using assistive technical devices as competent, attentive, and responsive, and are thus partly in line with our study. However, these studies do not include students with severe disabilities and do not give special attention to bodily expressions and existential dimensions to the same extent that we do and Moser (2006) and Shakespeare (2006) recommend.…”
Section: Discussionsupporting
confidence: 84%
“…Through qualitative interviews, Söderström and Ytterhus (2010) investigated how students with visual impairments/blindness experienced assistive technical devices as representing competence, belonging and independence as well as restriction, difference, and dependency. Söderström (2016) undertook an observational study including conversational interviews. She found that socio-material practices presented double-edged swords, where students moved between social participation and social isolation.…”
Section: Existing Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of studies conducting research on severely disabled children and their communicative challenges has increased in recent years. These studies have found that severely disabled children are able to communicate when adults and peers offer them an opportunity to be heard through their use of alternative and augmentative communication (Söderström, 2016;Evensen, Standal & Ytterhus, 2017;Østvik, Balandin & Ytterhus, 2018;Doak, 2018;Iacono, 2019;Ytterhus & Åmot, 2019). None of these studies have been carried out in small group homes, but rather in educational settings and schools.…”
Section: Voices Of Disabled Children Living In Residential Carementioning
confidence: 99%
“…Olaussen (2010) has studied the experience of hard of hearing and its relation to disability, technologies, practices, and politics. Another inspiration for us is work by Söderström (2009aSöderström ( , 2009bSöderström ( , 2016 who, in different ways, has traced children/youths with different disabilities/without disabilities relations to technologies (mobile phones, ICT, assistive technologies, etc.). These scholars share a mutual interest of how disability is enacted as part of relations among others: bodies, technologies, working practices, and policy documents.…”
Section: Introductionmentioning
confidence: 99%